Informatiom about XX Anniversary International Conference on Physics and Technology of Thin Film and Nanosystems (ICPTTFN-XX) - ICPTTFN-XX, Organizing Committee (Physics and Chemistry of Solid State, 2025)
October 6-10, 2025 TOPICS Thin films technology and research methods. Theoretical investigation: thin films and nanomaterials. Physical-chemical properties of thin films. Nano- and thin films applications: energy, biotechnology & medicine, defense, space, etc. Functional crystalline materials and materials with nanoinclusions. Nano- and Thin films: History of inventions and features of University’s educational programs.